Fabrication of high performance pvdf hollow fiber membrane using less toxic solvent at different additive loading and air gap - Suriani Abu Bakar (Tanjong Malim, 2021)
Fabrication of high performance pvdf hollow fiber membrane using less toxic solvent at different additive loading and air gap by Suriani Abu Bakar